APLIKASI WORDWALL DALAM MENINGKATKAN MOTIVASI BELAJAR: ANALISIS PEMBELAJARAN PANCASILA DI LAB SCHOOL UNIVERSITAS PGRI SEMARANG - Arti, Helmi; Sudrajat, Rahmat; Sutono, Agus (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
This study was carried out with the rapid development of technology affecting the world of education, varied learning media is a demand for educators to increase students' learning motivation due to internal and external factors (such as students feeling bored when class time starts until it ends, students feeling a lack of enthusiasm for learning when teachers use the lecture method, especially class XI). This research is intended as a form of knowledge about the Wordwall application to increase student learning motivation. This research uses a qualitative descriptive method with Abraham H. Maslow's learning motivation theory approach. Data collection techniques include observation, interviews, and documentation. This research produced information on the wordwall application to increase student learning motivation in Pancasila Education subjects at UPGRIS Laboratory High School. In this research, the indicators for designing, analyzing, implementing, evaluating, identifying, and recommending the implementation of the wordwall application are appropriate. However, the implementation process still has obstacles, namely that it requires quite a lot of time planning and the student's network devices are not yet optimal. several factors become obstacles in its implementation, namely having to enter, adjust, and choose a system in the application to enter material and student network devices that are not yet optimal. In this way, teachers must manage their time well and the school must improve adequate Wifi network equipment